LZM008, a proposed tocilizumab biosimilar: Pharmacokinetics, safety, and immunogenicity profiles compared with ACTEMRA® in Chinese healthy male subjects - Cao, Guoying; Wang, Jingjing; He, Jinjie; Hu, Yingying; Yang, Haijing; Que, Linling; Gu, Xianghong; Yu, Jicheng; Wu, Xiaojie; Wu, Jufang; Fang, Wei; He, Qing; et al. (Frontiers in pharmacology, 2023)
Background: This study aimed to investigate the pharmacokinetics, safety, and immunogenicity of recombinant humanized anti-human IL-6R monoclonal antibody injection, LZM008, and evaluate the pharmacokinetic similarity between LZM008 and tocilizumab (ACTEMRA ® ) in Chinese healthy male subjects. Research design and methods: In this randomized, double-blinded, paralleled, two-center Phase I clinical trial, 96 subjects were randomized with a 1:1 ratio to receive 4 mg/kg intravenous dose of LZM008 or ACTEMRA ® and evaluated for 28 days. The pharmacokinetic bioequivalence was assessed by the maximum serum concentration (C max ), the area under the serum concentration–time curve (AUC) from time 0 to the last detectable drug concentration (AUC 0-t ), and AUC 0-∞ . The statistical analysis was conducted using SAS Enterprise Guide statistical software. Safety was assessed by physical examinations, vital signs, laboratory tests, and electrocardiograms. Anti-drug antibodies (ADAs) were measured by a bridged electrochemiluminescence immunoassay. Results: LZM008 (N = 49) and ACTEMRA ® (N = 47) groups showed similar pharmacokinetic properties. After a single intravenous infusion of 4 mg/kg LZM008, the C max and AUC 0-∞ values of LZM008 reached 87.99 μg/mL and 11,526.70 h*μg/mL, respectively, with T max 1.98 h, and the half-life (t 1/2 ) was 83.45 h. The 90% confidence intervals of ratios for C max , AUC 0-t , and AUC 0-∞ were within the range of 80.00%–125.00%. After infusion, one (2.0%) subject in the LZM008 group and three (6.4%) subjects in the ACTEMRA ® group showed positive ADA test results. The incidence of treatment emergent adverse events (TEAEs) was comparable in LZM008 and ACTEMRA ® groups (98.0% versus 100%), with the decrease in blood fibrinogen and neutrophil counts being the most common TEAEs. Conclusion: The pharmacokinetic characteristics and immunogenicity exhibited by LZM008 were similar to those of the reference product, ACTEMRA ® . The safety profiles of LZM008 were similar in the two groups with mild–moderate adverse effects. Trial Registration: The trial is registered at www.chinadrugtrials.org.cn (CTR20190889).